Experiences with the use of European Union resources in the Southern Great Plain region (Hungary) in 2007-2008 - Vajda, Gizella (Hungarian Geographical Bulletin, 2010)
From the very formation of the European Union there have existed regions with different natural and social endowments. This causes a diversity in living conditions, income, and maturity within the integration. To reduce the socio-economic disparities between regions, and to raise the lagging ones are the major tasks within the EU in order to strengthen social and economic cohesion. The 2007–2013 year planning period for the first time opened an opportunity for the regions to develop separate operational programs in the EU. The present study summarizes the results of a survey which examined the direct or indirect resources that arrived into the region during the fi rst two years (2007–2008) of the Southern Great Plain’s Operational Program (SGPOP). An analysis is made how the EU funds were used, which part of the regional operational program was financed from them and how the mechanism for resource allocation worked.